WESTERN MILITARY CULTURE AND COUNTERINSURGENCY: AN AMBIGUOUS REALITY - Kitzen, Martijn (Scientia Militaria - South African Journal of Military Studies, 2012)
Contemporary campaigns in Iraq and Afghanistan once again have demonstrated that conventional armies experience many problems in adapting to counterinsurgency operations. This article seeks an explanation for those problems by exploring the conceptual background of both Western-style conventional armies and counterinsurgency. In essence, Western military culture is about fighting large-scale decisive battles with armies of other states. This contrasts strongly with counterinsurgency, which is about outbidding the insurgents for the favour of the people with a minimised use of force. The article analyses the further consequences of this conceptual clash between Western military culture and counterinsurgency in the reality of counterinsurgency warfare. It is explained that the contrast between both concepts leads to an ambiguous reality in which soldiers are aware of the specifics of counterinsurgency theory, but refer back to Western military culture for fighting counterinsurgency campaigns.